ROLE OF HUMIC ACID IN IMPROVING GROWTH CHARACTERS OF CORN UNDER WATER STRESS - & Ahmed, Abdulameer (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiment was carried out to study the role of humic acid in improving some growth characters of corn (Zea mays L.) under water stress conditions during fall of seasons 2016, 2017, by using randomized complete block  design within split plot arrangement and three replications. The study consisted of three levels of water stress, when depleting 50, 60 and 70% of available water which was equivalent to 580, 420 and 340 mm season-1 respectively, and occupied the main plot, while the levels of humic acid 0, 40, 60 and 80 kg-1 were in sub plots. The results showed no significant differences between the treatments of depletion 50% and 60% of the available water in number of days to tasseling, number of leaves, leaf area, leaf area index, dry weight of the plant and the crop growth rate in both seasons. Plants under water70% depletion produced the lowest means for studied traits. The addition of humic acid with 80 kg h-1 had the highest plant height, number of leaves, leaf area, leaf index, dry matter and crop growth rate. The effect of interaction between two variables was significant for all the studied traits except the number of days to tasseling and number of leaves plant-1. It could be concluded that in the case of limitd irrigation water, It could be irrigation with 60% of the available water with 80 Kg ha-1 humic acid is practiced.